Chemical Composition and Amino Acids Profile of Leucaena leucocephala Seeds - Ahmed, Mohamed Elamin; Abdelati, Khadiga Abbas (International Journal of Poultry Science, 2009)
The utilization of grain legumes such as Leucaena leucocephala by the feed industry is limited because of uncertainty about their nutritional quality. Although the analyzed total amino acid and energy contents of many grain legumes are quite similar, their protein qualities and metabolizable energy values are quite variable. Leucaena leucocephala seeds were analyzed for chemical composition and amino acids profile. The analyzed nutrient composition indicated that leucaena seeds are potential source of protein and energy. The protein content was 31.1% and the calculated metabolizable energy of the seeds was 2573.26 kcal/kg. Amino acids profile of leucaena seeds were 1.39% lysine%, 0.36% methionine, 0.35% cystine, 2.62% arginine, 4.63% glutamic acid, 0.87% threonine, 1.38% glycine, 1.11% alanine, 1.11% valine, 0.93% isoleucine, 1.81% leucine and 0.71% methionine + cystine. Antinutritional Factors (ANFs) were 0.75% tannin and 697.50 mg/100g phytate. Leucaena seed was incorporated at 0, 3, 6, 9 and 12% in broiler chicks' diets. One hundred twenty one-day old unsexed broilers (Ross 308) were used. The performance revealed that, the overall feed intake and body weight gain were significantly (p